Metals and amyloid-β in Alzheimer's disease - Maynard, Christa J (Blackwell Science Inc, 2005)
Mounting evidence is demonstrating roles for the amyloid precursor protein (APP) and its proteolytic product Aβ in metal homeostasis. Furthermore, aberrant metal homeostasis is observed in patients with Alzheimer's disease (AD), and this may contribute to AD pathogenesis, by enhancing the formation of reactive oxygen species and toxic Aβ oligomers and facilitating the formation of the hallmark amyloid deposits in AD brain. Indeed, zinc released from synaptic activity has been shown to induce parenchymal and cerebrovascular amyloid in transgenic mice. On the other hand, abnormal metabolism of APP and Aβ may impair brain metal homeostasis as part of the AD pathogenic process. Aβ and APP expression have both been shown to decrease brain copper (Cu) levels, whereas increasing brain Cu availability results in decreased levels of Aβ and amyloid plaque formation in transgenic mice. Lowering Cu concentrations can downregulate the transcription of APP, strengthening the hypothesis that APP and Aβ form part of the Cu homeostatic machinery in the brain. This is a complex pathway, and it appears that when the sensitive metal balance in the brain is sufficiently disrupted, it can lead to the self-perpetuating pathogenesis of AD. Clinical trials are currently studying agents that can remedy abnormal Aβ–metal interactions.